Fatigue reliability evaluation of deck-to-rib welded joints in OSD considering stochastic traffic load and welding residual stress - Cui, C.; Zhang, Q.; Luo, Y.; Hao, H.; Li, Jun (Elsevier BV, 2018)
© 2018 Elsevier Ltd The welding residual stress has a prominent contribution to the fatigue damage in deck-to-rib joints of orthotropic steel decks. To estimate the fatigue reliability of deck-to-rib joints with the combined effect of welding residual stress and stochastic traffic flow, a simplified mechanical model is employed to analyze the combined effect of welding residual stress and vehicle-induced stress. The fatigue reliability assessment is conducted by considering the increases of both the traffic flow and the gross vehicle weight with the strain energy density based method. The results demonstrate that the obtained stochastic traffic flow model agrees well with that measured from the weigh-in-motion system, validating the accuracy of the established stochastic traffic flow model for the fatigue reliability analysis. From the calculated fatigue reliability indices with or without the effect of welding residual stress, it can be concluded that the welding residual stress has a prominent negative influence on the fatigue resistance. The effect of the increase of the gross vehicle weight is more significant than that with the increase of the traffic flow on the fatigue reliability, demonstrating that the growth of t he gross vehicle weight has a more detrimental impact on the fatigue service life.